Pengaruh Diskriminasi Pajak Terhadap Penggelapan Pajak Religiusitas Sebagai Variabel Moderasi - Ema Agustina Tina (Jurnal Literasi Akuntansi, 2025)
Purpose: The purpose of this study is to analyse the impact of pajak discrimination on pajak adoption, using religiusitas as a moderating variable. Method: The methodology used in this study employs quantitative research. This study's data was collected via a questionnaire, and the sample size was determined using the Snowball Sampling method. Finding: This study concludes that tax discrimination has a positive effect on tax evasion in MSMEs in DIY, but religiosity can weaken this effect. These findings emphasize the importance of a fair tax system as well as moral education and religious ethics to improve tax compliance. Research limitations include the use of questionnaires as the only data collection method and limited variable coverage. Future research is recommended to use the interview method and to add other independent variables, such as tax rates or tax justice, expand the sample, and consider additional moderating variables, such as tax morale or moral responsibility, to enrich the analysis of tax evasion.   Novelty: The novelty in this study lies in the integration of religiosity as a moderating variable in the relationship between tax discrimination and tax evasion, which has not been widely explored in previous studies. Different from previous studies that focus more on economic and regulatory factors, this study highlights how moral values and social norms can influence taxpayer behavior. In addition, this study provides a new perspective for tax authorities by emphasizing the importance of psychological and social-based approaches in designing more effective tax policies. Thus, this study contributes to the development of academic literature as well as providing practical insights for policymakers in creating a fairer tax system and increasing religious value-based tax compliance.The novelty in this study lies in the integration of religiosity as a moderating variable in the relationship between tax discrimination and tax evasion, which has not been widely explored in previous studies. Different from previous studies that focus more on economic and regulatory factors, this study highlights how moral values and social norms can influence taxpayer behavior. In addition, this study provides a new perspective for tax authorities by emphasizing the importance of psychological and social-based approaches in designing more effective tax policies. Thus, this study contributes to the development of academic literature as well as providing practical insights for policymakers in creating a fairer tax system and improving religious value-based tax compliance.